Strategi dakwah di masa pandemi: Studi pada Majelis Tabligh Pimpinan Pusat Aisyiyah - Devi Anggraeni; Imam Suprabowo (Islamic Communication Journal, 2022)
The Covid-19 pandemic condition requires all activities to be limited. All activities turned to virtual activities, which of course became a new challenge for da'wah activities. This study discusses how the Majelis Tabligh Pimpinan Pusat Aisyiyah (the Tablighi Assembly of the Central Leadership of Aisyiyah), as a women's organization that has religious authority, carries out a da'wah strategy in the pandemic era in facing the existing challenges. This study uses a descriptive qualitative approach with an interview method that examines public relations strategies consisting of fact finding, planning, communication, and evaluation. The results of this study are the Tablighi Assembly of the Central Leadership of Aisyiyah applies several principles of da'wah strategy during the pandemic, namely (1) using a social approach by being open, (2) applying the principle of professional achievement, (3) paying attention to psychological principles in seeing the recipients (mad'u), (4) developing Human Resources (HR) with trainings such as public speaking training and media training, and always monitoring and evaluating the implementation of da'wah. The implication is that the contextualization of da'wah strategies in responding to various social challenges is a necessity, one of which is public relations-based da'wah.***Kondisi pandemi Covid-19 mengharuskan semua aktivitas dibatasi. Semua kegiatan beralih ke kegiatan virtual, yang tentunya menjadi tantangan baru bagi kegiatan dakwah. Penelitian ini membahas tentang bagaimana Majelis Tabligh Pimpinan Pusat Aisyiyah, sebagai organisasi perempuan yang memiliki otoritas keagamaan, menjalankan strategi dakwah di era pandemi dalam menghadapi tantangan yang ada. Kajian ini menggunakan pendekatan kualitatif deskriptif dengan metode wawancara yang mengkaji strategi humas yang terdiri dari pencarian fakta, perencanaan, komunikasi, dan evaluasi. Hasil kajin ini adalah Majelis Tabligh Pimpinan Pusat Aisyiyah menerapkan beberapa prinsip strategi dakwah di masa pandemi, yaitu (1) menggunakan pendekatan sosial dengan bersikap terbuka, (2) menerapkan prinsip pencapaian profesional, (3) memperhatikan prinsip psikologis dalam melihat penerima dakwah (mad'u), (4) mengembangkan Sumber Daya Manusia (SDM) dengan pelatihan-pelatihan seperti pelatihan public speaking dan pelatihan media, dan selalu melakukan monitoring dan evaluasi pelaksanaan dakwah. Implikasinya, kontekstualisasi strategi dakwah dalam menjawab berbagai tantangan sosial menjadi sebuah keniscayaan, yang salah satunya adalah dakwah berbasis kehumasan.